2022
DOI: 10.3389/fneur.2022.891514
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Clinical Efficacy of Mesenchymal Stem Cell Treatment in Traumatic Spinal Cord Injury, Multiple Sclerosis and Ischemic Stroke – A Systematic Review and Meta-Analysis

Abstract: BackgroundMesenchymal stem cells (MSCs) is an attractive candidate in regenerative research and clinical trials have assessed their therapeutic potential in different neurological conditions with disparate etiologies. In this systematic review, we aimed to assess safety and clinical effect of MSC treatment in traumatic spinal cord injury (TSCI), multiple sclerosis (MS) and ischemic stroke (IS).MethodsA systematic search was performed 2021-12-10 in MEDLINE, EMBASE, Web of Science and Cochrane where clinical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 68 publications
0
12
0
1
Order By: Relevance
“…In Kvistad CE. et al., review, fever and headache were the most common AEs, irrespective of administration mode [ 57 ]. Analysis of AEs in twelve studies with 502 patients receiving mesenchymal stem cell transplantation showed that the commonly reported mild AEs included fever, headache, and neuropathic pain [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Kvistad CE. et al., review, fever and headache were the most common AEs, irrespective of administration mode [ 57 ]. Analysis of AEs in twelve studies with 502 patients receiving mesenchymal stem cell transplantation showed that the commonly reported mild AEs included fever, headache, and neuropathic pain [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The administration of MSCs have also been assessed in SCI, either via intrathecal or intraoperative injections ( 145 ). Similar to the trials assessing NSCs, most of these were open-label trials designed to show feasibility and safety without a control group.…”
Section: Promotion Of Neural Regeneration In Spinal Cord Injury Multi...mentioning
confidence: 99%
“…-Dans la SEP progressive, plusieurs essais cliniques suggèrent un effet potentiel de la greffe de cellules souches mésenchymateuses sur la progression du handicap que ce soit par voir IV ou par voie intra thécale 21,22 . D'autres maladies neurologiques, comme la chorée de huntington, l'AVC ischémique, la maladie d'alzeihmer font également l'objet d'essais cliniques de thérapie cellulaire.…”
Section: Quelles Cellules Pour Quelles Applications En Neurologie ?unclassified